Editorial - Smart energy systems and 4th generation district heating systems - Østergaard, Poul Alberg; Lund, Henrik; Mathiesen, Brian Vad (International Journal of Sustainable Energy Planning and Management, 2018)
This editorial introduces the 16th volume of the International Journal of Sustainable Energy Planning and Management, which addresses different angles of district heating ranging from the planning of district heating systems and economic incentives for flexible district heating plants to comparisons between low and ultra-low-temperature district heating systems and methods for determining thermal conductivity in district heating pipes.